Promotion of Sustainable Consumption in the Energy Sector - Buzoianu, Ovidiu Andrei Cristian; Constantinescu, Victor George; Troaca, Victor Adrian; Dima, Cristina (European Journal of Sustainable Development, 2023)
Sustainable development as it is currently framed aims to reduce the consumption of available resources while minimizing negative impacts on the environment. Sustainability encompasses ecological, economic and social concerns. A main purpose of this term is the maintenance and development of human well-being on a local and global scale. So that this term can be approached by the population, all its attributions must be appropriated and understood. The existence of ecological conditions is necessary to lead an economically sustainable lifestyle. A control over nature and ideas of balance between human effort and nature, fostered by sustainable desolation can benefit future generations. The relevance of such an ecological balance is assessed by comparing how consumption typically occurs in modern human societies as opposed to nature. Sustainable consumption emphasizes the term "green consumption" and reducing the carbon footprint. Key words: consumption, development, energy, sustainability